A fire deficit persists across diverse North American forests despite recent increases in area burned - Parks, Sean A.; Guiterman, Christopher H.; Margolis, Ellis Q.; Lonergan, Margaret; Whitman, Ellen; Abatzoglou, John T.; Falk, Donald A.; Johnston, James D.; Daniels, Lori D.; Lafon, Charles W.; Loehman, Rachel A.; Kipfmueller, Kurt F.; et al. (Nature communications, 2025)
Rapid increases in wildfire area burned across North American forests pose novel challenges for managers and society. Increasing area burned raises questions about whether, and to what degree, contemporary fire regimes (1984–2022) are still departed from historical fire regimes (pre-1880). We use the North American tree-ring fire-scar network (NAFSN), a multi-century record comprising >1800 fire-scar sites spanning diverse forest types, and contemporary fire perimeters to ask whether there is a contemporary fire surplus or fire deficit, and whether recent fire years are unprecedented relative to historical fire regimes. Our results indicate, despite increasing area burned in recent decades, that a widespread fire deficit persists across a range of forest types and recent years with exceptionally high area burned are not unprecedented when considering the multi-century perspective offered by fire-scarred trees. For example, ‘record’ contemporary fire years such as 2020 burned 6% of NAFSN sites—the historical average—well below the historical maximum of 29% sites that burned in 1748. Although contemporary fire extent is not unprecedented across many North American forests, there is abundant evidence that unprecedented contemporary fire severity is driving forest loss in many ecosystems and adversely impacting human lives, infrastructure, and water supplies. Across many North American forests, recent years with exceptional area burned are not unprecedented when considering the multi-century perspective offered by fire-scarred trees. Nevertheless, abundant evidence suggests that the severity of contemporary wildfire is unprecedented in its adverse impacts on forests and humans.